2023
DOI: 10.3390/ijerph20075416
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Behaviors in Quality of Life: A Longitudinal Study of Patients with Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the third most common malignancy and the second most common cancer-related cause of death worldwide. CRC incidence depends, in part, on the health behaviors that make up an individual’s lifestyle. We aimed to assess the influence of health behaviors and quality of life (QoL) among patients with CRC receiving surgical treatment. In this single-center questionnaire study, 151 patients were surveyed 1 week before and 6 months after colorectal procedures (laparoscopic hemicolectomy, low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…In the present study, the effect of smoking on HRQOL failed to reach statistical significance, possibly due to the relatively small number of smokers observed (seven current smokers [10.0%] and eight former smokers [11.4%]) and the follow-up period only being 9 months. Therefore, previous findings of lower HRQOL in smokers [ 33 , 34 ] cannot be confirmed by the results of the present study. A larger sample size and a longer follow-up period may have greater statistical power to detect the effects of smoking on HRQOL.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the effect of smoking on HRQOL failed to reach statistical significance, possibly due to the relatively small number of smokers observed (seven current smokers [10.0%] and eight former smokers [11.4%]) and the follow-up period only being 9 months. Therefore, previous findings of lower HRQOL in smokers [ 33 , 34 ] cannot be confirmed by the results of the present study. A larger sample size and a longer follow-up period may have greater statistical power to detect the effects of smoking on HRQOL.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, each patient will receive a comprehensive psychological, symptom and survivorship care needs assessment that is carried out at the beginning of the therapy, so that individualized TCM and supportive care plans can be integrated into the related session. So far, several studies have proved that education on lifestyle and health behavior has positive impact on CRC patients' quality of life 20,21 . To the best of our knowledge, the current study is one of the rst to integrate methods and opinions of TCM into such education program and group therapy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, white meat such as fish and poultry is secure and not linked with colorectal cancer development [ 199 ]. It has been shown, however, that nutrition rich in dietary fiber, including fruit, vegetables, and cereals, is connected with a decrease in the risk of CRC by up to 50% [ 200 ]. A prospective study reported that fiber consumption from bread and breakfast cereals is linked with a 14% reduced danger of colorectal cancer [ 199 ].…”
Section: Lifestyle and Colorectal Cancermentioning
confidence: 99%